The burden of asymptomatic sexually transmitted infections among men in Carletonville, South Africa: implications for syndromic management. Issue 5 (2nd April 2008) - Lewis, D A; Pillay, C; Mohlamonyane, O; Vezi, A; Mbabela, S; Mzaidume, Y; Radebe, F
Abstract : Objectives: To determine the prevalence of sexually transmitted infections (STI) and HIV among men attending an outreach STI/HIV screening service in informal settlements in South Africa over a 3-month period. Methods: A mobile clinic van was utilised to offer men: (1) urine screening for gonorrhoea, trichomoniasis, chlamydial and Mycoplasma genitalium infections; (2) serological screening for syphilis and herpes simplex virus type 2 (HSV-2); (3) on-site HIV voluntary counselling and testing. Urethritis pathogens were detected by molecular methods. HIV serostatus was determined using rapid tests. Demographic, sexual behaviour and clinical data were recorded on a nurse-administered questionnaire. Statistical analysis utilised the χ 2 test. Results: 309 men attended the service; 304 (98%) requested serological screening for syphilis and HSV-2, 301 (97%) underwent urine-based screening for urethritis pathogens and 269 (87%) had an HIV test. Over 90% of men were asymptomatic for STI. Gonorrhoea was more prevalent in the symptomatic group (p<0.001); there were no significant differences in the prevalence of other urethritis pathogens between the groups. The total number of infections with each urethritis pathogen was highest in the asymptomatic group with twice as much gonorrhoea, 25 times as much chlamydial infection, six times as much trichomoniasis and nine times as much M genitalium infection compared with the symptomatic group. The overall HIV prevalence among clinic attendees was 29.7%. Conclusions: The uptake of both STI and HIV testing was high among men attending the service. The relatively high burden of both STI and HIV among the male clinic attendees has implications for the transmission of HIV.